Colorectal cancer patient outcome is influenced by tumour-adherent bacteria through epigenetic regulation of cardinal genes including PHLPP1 - Mathias Chamaillard; Khashayarsha Khazaie; Cécile Charpy; Iradj Sobhani; Aurelien Amiot; Nilmara De Oliveiro Alves; Emma Bergsten; Caroline Barau; Amaury Vaysse; Shatha Awaad; Mohammad Sadeghi; Denis Mestivier (BMJ Oncology)
Objective How tumour-adherent microbiome can influence outcomes in patients with colorectal cancer (CRC).Methods and analysis CRC tissues (n=97) were analysed using RNAseq, whole exome sequencing (WES) and 16 r sRNA sequencing. Inflammatory/immune cells were quantified by immunohistochemistry in mice and human tissues. Patient outcomes were analysed according to virulent bacteria and gene RNA levels in tumour tissues. We performed faecal microbiota transfer (FMT) in germ-free mice using presurgery stool samples from nine patients with sporadic CRC. Changes in gene mutations and DNA methylation in the colonic mucosa were measured and compared with those in mice receiving FMT from nine healthy individuals. Immune cells in the tumour tissues of donor and mouse recipients were compared.Results FMT from CRC donors led to preferential DNA demethylation, but specific host genes, including pleckstrin homology domain and leucine-rich repeat protein phosphatase 1 (PHLPP1), were hypermethylated compared with FMT from healthy donors. CRC faecal samples showed elevated levels of virulent bacteria, reduced levels of commensals and triggered colon inflammation in mice. Notably, PHLPP1 was downregulated in CRC tumours, and its expression varied in accordance with other CRC cardinal genes (n=137, as identified in the scientific literature to be involved in colon carcinogenesis), and was most pronounced in inflammatory bowel disease associated CRC. Tumours with reduced PHLPP1 expression are more inflammatory and correspond to patients with a higher relative abundance of adherent virulent bacteria and poorer outcomes.Conclusion The composition of CRC tumour-adherent bacteria predicts epigenetic modifications and altered expression of cardinal CRC genes such as PHLPP1. PHLPP1 downregulation characterises patients with CRC with inflammatory tumours and poor survival outcomes.